Automatic Blood Collection and Mixer in a Blood Transfusion System Equiped with Barrier Indicators - Putra, Chandra Bimantara; Ariswati, Her Gumiwang; Sumber, Sumber; Zahar, Muzni (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
A blood collection monitor is a device used to measure and shake the blood bag during a blood transfusion so that the blood in the bag does not clot and is mixed with anticoagulant fluid in the bag properly. This study aims to design an automatic blood collection and mixer for the transfusion blood system. The advantage of the proposed design is accompanied by a safety system in the form of a barrier indicator that is connected to an alarm. The alarm served to give a warning to blood donors if there is an obstacle or there is no increase in volume as much as 20ml for 1 minute as recommended by the world blood bank association. This device can work with three different sizes of blood bags. In this study, a loadcell sensor is used to detect the amount of blood fluid that enters the bag. Furthermore, then it is converted into milliliter volume. In order to collect the blood, a shaker is drove using a motor controlled by Arduino microcontroller. From the measurement, for the entire size of the blood bag, we found that the deviation is 0, UA is 0, and the average error is 0. Thus, it can be concluded that this device can be used properly. In the future, it can be developed a blood infusion with the flowrate measurement to determine the speed of blood during donation